Materialne sledi kulture - Godina-Golija, Maja (Traditiones (Ljubljana), 2008)
Festive food and it s preparation, variety, wealth of different shapes, and regional diversity are the themes most of ten dealt with in ethnological literature. Apart from spiritual culture ethnographers were interested in certain elements of material culture already in the 19th century, believing that festive foods expres sed special characteristics and original features of a nation or an ethnic group. Ethnological texts dealing with other areas of food culture, for example with meals, eating habits, food culture of different social and age groups, or changes in tradition, have been rare. The author examines a less researched area of the food culture of Slovenes, namely festive food and meals, and their transformation in the 20th and in the 21st centuries.
Keywords: ethnology; etnologija; food; prehrana; ljudske šege; Slovenia; Slovenija; 20./21.st.